Hubungan antara Pengetahuan dan Sikap dengan Kesehatan Gigi dan Mulut Pada Mahasiswa keperawatan di Stikes Amanah Makassar - Alimuddin, Hadijah; Wati, Riska; Zaihafni, Yanda; Rahmadani, Nanang; Feblina, Ayu Rahayu; Adam, Andi Muh. Adam (Jurnal Ilmiah Amanah Akademika, 2022)
Dental and oral health is one of the benchmarks for assessing general health. Maintaining healthy teeth and mouth must be accompanied by good knowledge and the right attitude. The aim of this research is to determine whether there is a relationship between knowledge and attitudes towards maintaining oral health among students of the Stikes Amanah Makassar Nursing Study Program. Method: The research used is quantitative research with a cross-sectional approach. Sampling used a simple random sampling technique. Data was collected using a questionnaire. This research was conducted on Amanah Stikes Makassar nursing students with age criteria of 18-25 years. The calculation process focuses on gender and class consisting of transfer classes and regular classes in the nursing program and then calculated based on the total knowledge and attitude scoring. Results: The chi-square value of the total gender criteria table (p) cross tabulation was 0.713, while the chi-square value of the total class criteria table (p) cross tabulation was 0.554. The total chi-square value of the cross-tabulation gender criteria table is 0.264, while the chi-square value of the cross-tabulation total class criteria table is 0.832.